Influence of Trust and Perceived Value on Non-BPJS Patients’ Revisit Intentions Moderated by Hospital Image - Maria Stephanie; Duta Liana; Idrus Jusat (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2025)
In the healthcare sector, patient revisit intention serves as an important measure of hospital success, influencing financial stability, operational effectiveness, and long-term patient retention. With increasing competition, hospitals must strengthen trust, improve service quality, and maintain a positive institutional image to retain patients. This study focuses on the declining number of non-BPJS (non-insured) patients at Cinta Kasih Tzu Chi Hospital, Cengkareng, which impacts revenue sustainability. The research aims to assess how trust and customer perceived value affect revisit intention, and whether hospital image moderates these relationships. A quantitative approach was applied using a structured questionnaire distributed to 95 non-BPJS outpatients who had previously sought treatment more than once. Data were analyzed through Structural Equation Modeling (SEM) using the Partial Least Squares (PLS) method via SmartPLS software. The findings reveal that both trust and perceived value significantly and positively influence revisit intention, implying that patients with strong trust and satisfaction tend to return. Although hospital image directly influences revisit intention, it does not significantly moderate the link between perceived value and revisit intention. Therefore, hospitals are advised to enhance patient trust and perceived value while sustaining a credible institutional image to strengthen loyalty among non-BPJS patients